Kaderisasi Dalam Al-Qur’an : Studi Kata Dhi’afa Pada Surat An -Nisa ayat 9 - Hilyatun Najuba; Heri Khoiruddin (PT. ALHAFI BERKAH INDONESIA, 2023)
Strong human resources are very necessary for organizations in this modern era to run well. There are many events occurring and also the rapid development of the flow of information, making it difficult to find a leader who has integrity and strong character. Cadre formation is needed to train and prepare the next generation to have skills and scientific discipline, so that they can become a strong generation who have the ability to be ready to take on further responsibilities in each organization. The method used in this research uses a qualitative method using a munasabah approach. The research that the author uses is included in the type of library research. The results of this research found the weak meaning of the word Dhi'afu and several similar words with the same meaning in the letter. Cadre formation is an effort to maintain a strong generation so as not to leave the leadership of a weak generation. but strong from various aspects, namely strong in faith, financial, emotional, and knowledge.